Sulfide-based solid electrolyte, solid electrolyte layer, and lithium-ion secondary battery
By containing S8 molecules in the sulfur-silver germanium ore crystal structure, it makes it soft, and the problem of poor adhesion of sulfide-based solid electrolyte is solved, the lithium ion conductivity is improved and the use of binders is reduced, and lithium ion is realized The battery characteristics of secondary batteries are improved.
Patent Information
- Application Number
- CN202180075677.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-11-11
- Filing Date
- 2021-11-05
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2041-11-05
AI Technical Summary
The existing sulfur-silver germanium ore-type sulfide-type solid electrolytes have poor adhesion when processed into pressed powder, resulting in a decrease in lithium ion conductivity and tend to become brittle after applying a large pressure. It is necessary to add a binder to supplement the adhesion. but this reduces lithium ion conductivity.
By containing S8 molecules in the sulfur-silver germanium ore crystal structure, it is softened, thereby improving adhesion, good lithium ion conductivity when making pressed powder, and reducing dependence on binder.
The adhesion of the sulfide-based solid electrolyte is achieved, the battery characteristics of the lithium-ion secondary battery are improved, the lithium-ion conductivity is enhanced, and the amount of binder is reduced, thereby avoiding the reduction of lithium-ion conductivity.
Smart Images

Figure BDA0004218874230000191
Abstract
Description
Technical Field
[0001] The present invention relates to a sulfide-based solid electrolyte, a solid electrolyte layer and a lithium-ion secondary battery. Background Art
[0002] Lithium-ion secondary batteries are widely used in portable electronic devices such as mobile phones and laptops.
[0003] Until now, liquid electrolytes have been used in lithium-ion secondary batteries, but there are concerns about leakage and fire, and the outer casing needs to be enlarged for safety design. In addition, it is also expected to improve the problems of short battery life and narrow operating temperature range.
[0004] On the other hand, all-solid-state lithium ion secondary batteries using a solid electrolyte as the electrolyte of the lithium ion secondary battery are attracting attention from the viewpoints that they can be expected to achieve improved safety, high-speed charging and discharging, and miniaturization of the housing.
[0005] Solid electrolytes are roughly divided into sulfide-based solid electrolytes and oxide-based solid electrolytes. Sulfide ions have a larger polarizability than oxide ions and show high ion conductivity. As sulfide-based solid electrolytes, Li 10 GeP2S 12 LGPS type crystals, Li6PS5Cl and other argyrodite type crystals, Li7P3S 11 Crystallized glass, etc. LPS crystallized glass, etc.
[0006] As an example of a sulfide-based solid electrolyte of the argyrodite type, Patent Document 1 can be cited. The sulfide-based solid electrolyte disclosed in Patent Document 1 has a crystal structure belonging to the cubic system and the space group F-43m, and contains a composition formula of Li 7-x PS 6-x Ha x (Ha is Cl or Br) (x = 0.2 to 1.8), and L * a * b * The lightness L value of the color system is 60.0 or more. The purpose is to increase lithium ion conductivity, reduce electron conductivity, and thus improve charge and discharge efficiency and cycle characteristics.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: International Publication No. 2015 / 012042 Summary of the invention
[0010] When a sulfide-based solid electrolyte is used in a lithium-ion secondary battery, etc., the powdered sulfide-based solid electrolyte is sometimes processed into a granular, layered (sheet-like) or other compressed powder. However, a sulfide-based solid electrolyte having an argyrodite-type crystal structure is harder than, for example, LPS crystallized glass, and the adhesion between the powders is poor.
[0011] In such an argyrodite-type sulfide-based solid electrolyte, a large pressure needs to be applied in order to make the powder sufficiently close together and improve the lithium ion conductivity of the powder compact. In addition, if a large pressure is applied, although it can be processed into a powder compact, the obtained powder compact tends to become brittle. Therefore, in order to maintain the strength of the powder compact, a binder or the like needs to be added to supplement the close adhesion. If the amount of the binder or the like added increases, the proportion of the sulfide-based solid electrolyte in the powder compact becomes relatively small, and there is a concern that the lithium ion conductivity of the powder compact will decrease.
[0012] Therefore, an object of the present invention is to provide a sulfide-based solid electrolyte in which a powder compact exhibits good lithium ion conductivity by making the adhesion excellent.
[0013] The present inventors conducted intensive research and found that by including sulfur in the state of S8 in the crystal structure of a sulfide-based solid electrolyte having a argyrodite-type crystal structure, the sulfide-based solid electrolyte becomes relatively soft, thereby obtaining a sulfide-based solid electrolyte having excellent adhesion when made into a powder compact, thereby completing the present invention.
[0014] That is, the present invention relates to the following [1] to [7].
[0015] [1] A sulfide-based solid electrolyte used in a lithium-ion secondary battery,
[0016] A crystal structure of the argyrodite type containing Li, P, S and Ha,
[0017] The above-mentioned Ha is at least one selected from F, Cl, Br, and I,
[0018] In the Raman spectrum obtained by Raman spectroscopy, the -1 、205~235cm -1 and 460~490cm -1 There is a peak at least at one of
[0019] In the DSC curve obtained by differential scanning calorimetry (DSC), there is no endothermic peak in the range of 70 to 160°C.
[0020] [2] The sulfide-based solid electrolyte according to [1] above, wherein the crystal structure is composed of Li a PS b Ha c (5≤a≤7, 4≤b≤6 and 0<c≤2) represents.
[0021] [3] The sulfide-based solid electrolyte according to [1] or [2], wherein in the Raman spectrum, 420 to 440 cm -1 The peak intensity (I A ) and 460~490cm -1 The peak intensity (I B ) B / I A It is 0.005 or more.
[0022] [4] The sulfide-based solid electrolyte according to any one of [1] to [3] above, wherein when the sulfide-based solid electrolyte is in a powder state with an average particle size of 2 to 10 μm,
[0023] The ratio σ(30kN) / σ(10kN) of the lithium ion conductivity σ(30kN) at 25°C of the powder pressed at a pressure of 30kN to the lithium ion conductivity σ(10kN) at 25°C of the powder pressed at a pressure of 10kN is 1.34 or less.
[0024] [5] The sulfide-based solid electrolyte according to any one of [1] to [4] above, wherein the elastic modulus is 5 to 40 GPa.
[0025] [6] A solid electrolyte layer comprising the sulfide-based solid electrolyte according to any one of [1] to [5] above.
[0026] [7] A lithium ion secondary battery comprising the sulfide-based solid electrolyte according to any one of [1] to [5] above.
[0027] According to the sulfide-based solid electrolyte of the present invention, the adhesion when a powder compact is made from a powder state is excellent, so it is easy to obtain a powder compact showing good lithium ion conductivity. By using the sulfide-based solid electrolyte of the present invention as a solid electrolyte for a lithium ion secondary battery, it is expected that the battery characteristics of the lithium ion secondary battery will be improved. DETAILED DESCRIPTION
[0028] The present invention is described in detail below, but the present invention is not limited to the following embodiments and can be arbitrarily changed without departing from the gist of the present invention. In addition, when "~" representing a numerical range is used, it means that the numerical values recorded before and after it are included as the lower limit and upper limit. In this specification, sulfide-based solid electrolytes are sometimes referred to as "solid electrolytes". In this specification, the ratio (percentage, etc.) of the weight basis is the same as the ratio (percentage, etc.) of the mass basis.
[0029] <Sulfide-based solid electrolyte>
[0030] The sulfide-based solid electrolyte involved in the embodiment of the present invention (hereinafter also referred to as "the present solid electrolyte") is used for lithium-ion secondary batteries. The present solid electrolyte contains a argyrodite-type crystal structure containing Li, P, S and Ha (hereinafter also referred to as "argyrodite-type crystal"). Here, Ha is at least one selected from F, Cl, Br, and I. In addition, the present solid electrolyte has a bonding peak of S8 in the Raman spectrum obtained by Raman spectroscopy, and there is no endothermic peak attributable to the phase change and melting of sulfur in the DSC curve obtained by differential scanning calorimetry (DSC). That is, the present solid electrolyte has a bonding peak of S8 in the Raman spectrum at 140 to 170 cm -1 、205~235cm -1 and 460~490cm -1 There is a peak at least at one or more locations in the DSC curve, and there is no endothermic peak in the range of 70 to 160°C.
[0031] The present solid electrolyte comprises a argyrodite-type crystal structure containing Li, P, S and Ha. The halogen element represented by Ha is at least one selected from F, Cl, Br, and I. Argentodite-type crystals may contain only one of the same composition, or may contain two or more of different compositions.
[0032] The halogen element is at least one selected from F, Cl, Br, and I, but from the perspective that the crystal is easily converted into an argyrodite type, it is preferably at least one of Cl and Br, more preferably Cl, and further preferably a single substance of Cl or a mixture of Cl and Br.
[0033] The crystal structure can be analyzed based on the powder X-ray diffraction (XRD) pattern. In the XRD pattern, there are peaks at 2θ=15.7±0.5° and 30.2±0.5°, so it can be said that the crystal is argyrodite-type. In addition to the above, the XRD pattern preferably has a peak at 2θ=18.0±0.5°, and more preferably has a peak at 2θ=25.7±0.5°.
[0034] A preferred crystal structure is a cubic system (eg, F-43m), but there may also be rhombohedral systems, tetragonal systems, orthogonal systems with reduced symmetry, and there may also be monoclinic systems with further reduced symmetry.
[0035] In the present solid electrolyte, the argyrodite-type crystal structure contains S8 molecules in its crystal structure. It should be noted that "containing S8 molecules in the crystal structure" includes not only the case where the S8 molecules enter the interior of the crystal structure, but also the case where the S8 molecules exist outside the argyrodite-type crystal structure but are uniformly dispersed in the grain boundaries between crystals. That is, it can be considered that in the present solid electrolyte, the S8 molecules are in a state of being uniformly dispersed in at least one of the interior of the crystal structure and the grain boundaries between crystals.
[0036] The elastic modulus of sulfur as a crystallinity of S8 molecules is relatively low. That is, it can be said that the S8 molecular structure is relatively soft. Therefore, the S8 molecules are uniformly present in the argyrodite-type crystal structure, making the crystal relatively soft, that is, the elastic modulus becomes small. Thus, the adhesion of the solid electrolyte can be improved.
[0037] In contrast, in the case where the argyrodite-type crystals and S8 molecules are separated and exist in an uneven state, in other words, in the case where the region formed by the aggregation of S8 molecules exists in the solid electrolyte, it can be considered that the group of S8 molecules becomes a resistance layer, which hinders the lithium ion conduction of the crystal. In addition, the elastic modulus of the region where the S8 molecules are aggregated is easily reduced locally, and the strain is easily concentrated in this part. Therefore, it can be considered that if such a region exists, it is difficult to uniformly apply pressure to the solid electrolyte. That is, the present solid electrolyte becomes a relatively soft and uniform crystal by uniformly containing S8 molecules in the crystal structure, and the lithium ion conductivity is also excellent.
[0038] In the Raman spectrum obtained by Raman spectroscopy, the present solid electrolyte has a bonding peak of S8. On the other hand, in the DSC curve obtained by differential scanning calorimetry (DSC), the present solid electrolyte has no endothermic peaks attributable to the phase change and melting of sulfur. Having a bonding peak of S8 in the Raman spectrum means that the solid electrolyte contains S8 molecules. In contrast, the absence of an endothermic peak of sulfur in the DSC curve means that, in the solid electrolyte, there is no sulfur that is separated from the argyrodite-type crystal structure and exists as a group of S8 molecules. If it is a solid electrolyte having a region where S8 is separated from the argyrodite-type crystal structure and S8 molecules exist in groups, there is an endothermic peak of sulfur in the DSC curve. Therefore, there is a bonding peak of S8 in the Raman spectrum, and there is no endothermic peak attributable to the phase change and melting of sulfur in the DSC curve, so that it can be judged that the present solid electrolyte contains S8 molecules in the crystal structure.
[0039] It should be noted that in a substance containing S8 molecules uniformly in the crystal structure like the present solid electrolyte, there will also be a difference in the particle size distribution after crushing compared to an inhomogeneous solid electrolyte in which argyrodite-type crystals and S8 exist separately. That is, the deviation of the particle size after crushing of the present solid electrolyte tends to become smaller, and the shape of the particle size distribution tends to become sharp, but in an inhomogeneous solid electrolyte, the deviation of the particle size after crushing tends to become larger, and the shape of the particle size distribution becomes broad and blunt. The particle size distribution can be confirmed by measuring with a laser diffraction particle size distribution meter.
[0040] The S8 bonding peak in the Raman spectrum specifically refers to the Raman shift of 140 to 170 cm from the S-S bond of the S8 molecule. -1 、205~235cm -1 and 460~490cm -1 That is, in the Raman spectrum, the solid electrolyte has a peak in the range of 140 to 170 cm -1 、205~235cm -1 and 460~490cm -1 There is a peak in at least one of the above.
[0041] It should be noted that the Raman spectrum obtained by Raman spectroscopy does not particularly change depending on the measurement conditions, but generally refers to a spectrum obtained under the conditions of an excitation light wavelength of 532 nm and a power of 1 to 3 mW.
[0042] The endothermic peak from the phase change of sulfur in the DSC curve specifically refers to the endothermic peak near 90-115°C from the change from the α-type state to the β-type. The endothermic peak from the melting of sulfur specifically refers to the endothermic peak near 115-140°C from the change from the solid state to the liquid. Here, "near" refers to, for example, a range within ±20°C. Therefore, since there is no endothermic peak in the DSC curve of the present solid electrolyte within the range of 70-160°C, it can be confirmed that there is no endothermic peak attributable to phase change or melting. In the case where S8 is contained in the crystal structure as in the present solid electrolyte, it can be considered that a argyrodite-type crystal is arranged adjacent to the S8 molecule. Therefore, it can be considered that since the S8 molecule is not accompanied by thermodynamic state changes such as phase change and melting, such an endothermic peak cannot be confirmed.
[0043] In this specification, the DSC curve obtained by differential scanning calorimetry (DSC) means a curve obtained under the conditions of a temperature increase rate of 5°C / min and a measurement temperature range of 25°C to 300°C.
[0044] The crystal structure of the argyrodite type is composed of Li a PS b Ha c(5≤a≤7, 4≤b≤6 and 0<c≤2) represents.
[0045] Here, from the viewpoint of achieving high lithium ion conductivity, c, which represents the content ratio of Ha, is preferably 0.5 or more, more preferably 1 or more, and further preferably 1.5 or more. In addition, from the viewpoint of suppressing corrosion of the metal collector, c is preferably 1.9 or less, more preferably 1.8 or less, and further preferably 1.7 or less.
[0046] It should be noted that the above Li a PS b Ha c The composition includes S including S8 in the crystal structure.
[0047] Here, the general argyrodite crystal tends to be sulfur-deficient, so the a:b:c ratio in the general argyrodite solid electrolyte tends to be
[0048] The tendency of (6-x):(5-x-y):(1+x) (y is 0≤y≤1).
[0049] On the other hand, since the present solid electrolyte has S8 added to the general argyrodite crystal, if the amount of S8 is set to z (z is 0<z≤2), a:b:c in the present solid electrolyte can be
[0050] (6-x):(5-x-y+z):(1+x).
[0051] The composition can be analyzed by appropriately combining ICP emission spectrometry, atomic absorption spectrometry, ion chromatography and the like.
[0052] In addition, the content of S8 in the solid electrolyte can be determined by the Raman spectrum at 420-440 cm -1 The position observed from PS4 3- The peak intensity (I A ) and at 460~490cm -1 The peak intensity from S8 observed at the position (I B ) B / I A From the viewpoint of improving adhesion, the Raman spectrum of 420 to 440 cm -1 The peak intensity (I A ) and 460~490cm -1 The peak intensity (I B ) B / I A It is preferably 0.005 or more, more preferably 0.007 or more, and still more preferably 0.01 or more. In addition, from the viewpoint of suppressing the decrease in lithium ion conductivity, IB / I A It is preferably 0.5 or less, and more preferably 0.3 or less.
[0053] From the viewpoint of obtaining good lithium ion conductivity when the solid electrolyte is finely crushed and converted into a battery, the crystallite size of the argyrodite-type crystal is preferably smaller, specifically, preferably less than 1000 nm, more preferably less than 500 nm, and further preferably less than 250 nm. The lower limit of the crystallite size is not particularly limited, but is generally greater than 5 nm.
[0054] The crystallite size after the heat treatment becomes larger than that before the heat treatment, but it is preferable that the crystallite size remains within the above range even after the heat treatment.
[0055] The crystallite size can be calculated using the Scherrer equation for the half-value width of the peak in the XRD pattern.
[0056] As one of the criteria for evaluating the adhesion of the present solid electrolyte, the ratio σ(30kN) / σ(10kN) of the lithium ion conductivity σ(30kN) when the powder is made into a powder compact at a pressure of 30kN and the lithium ion conductivity σ(10kN) when the powder is made into a powder compact at a pressure of 10kN can be used. Here, the average particle size refers to the D50 average particle size (median particle size: the particle size at which the cumulative frequency is 50% on a volume basis). The average particle size can be obtained, for example, by a particle size distribution measuring device. In addition, in this specification, the lithium ion conductivity σ is used at 25°C unless otherwise specified.
[0057] It should be noted that the present solid electrolyte having an average particle size of 2 to 10 μm can be further finely pulverized to form a powder state having an average particle size of less than 2 μm, depending on the application, etc. In this case, the ratio σ'(30 kN) / σ'(10 kN) of the lithium ion conductivity σ'(30 kN) when the powder having an average particle size of less than 2 μm is formed into a powder compact at a pressure of 30 kN to the lithium ion conductivity σ'(10 kN) when the powder having an average particle size of less than 2 μm is formed into a powder compact at a pressure of 10 kN is greater than the ratio σ(30 kN) / σ(10 kN) when the powder having an average particle size of 2 to 10 μm is formed.
[0058] When a solid electrolyte in a powder state is processed into a powder compact for use, the closer the powder particles are to each other, the higher the lithium ion conductivity of the powder compact. This is believed to be because the larger the contact interface between the particles, the smaller the grain boundary resistance at the interface between the powder particles.
[0059] If the same powder is pressed into a powder compact with a greater pressure, the adhesion is improved, and the lithium ion conductivity is increased accordingly. However, when the pressure is increased to a certain level, the lithium ion conductivity reaches an upper limit (maximum conductivity), that is, it no longer increases. The smaller the pressure required to make the powder compact have the maximum conductivity, the smaller the pressure can be used to make the powder sufficiently close, that is, the powder can be evaluated as having good adhesion.
[0060] For powders that require a relatively high pressure to achieve maximum conductivity, although a large pressure can be applied to form a compressed powder, the resulting compressed powder tends to become brittle. In such a case, in order to maintain the strength of the compressed powder, a binder or the like must be added to supplement the tightness. If the amount of binder or the like added increases, the proportion of sulfide-based solid electrolytes in the compressed powder becomes relatively small, and there is a concern that the lithium ion conductivity of the compressed powder may be reduced. Therefore, if the powder has good tightness, it is not only easy to achieve maximum conductivity with a smaller pressure, but also the amount of binder or the like added can be suppressed, increasing the proportion of sulfide-based solid electrolytes in the compressed powder, resulting in an increase in the lithium ion conductivity of the compressed powder.
[0061] That is, σ(30 kN) / σ(10 kN) is usually greater than 1, but the smaller the value of σ(30 kN) / σ(10 kN), the closer it is to 1, and the smaller the pressure required to make the powder compact have the maximum conductivity. σ(30 kN) / σ(10 kN) is preferably less than 1.34, more preferably less than 1.32, and even more preferably less than 1.3.
[0062] In addition, from the perspective of obtaining good battery characteristics when used in lithium ion secondary batteries, the lithium ion conductivity σ(30kN) of the present solid electrolyte is preferably 0.1mS / cm or more, more preferably 0.5mS / cm or more, and further preferably 1mS / cm or more. The larger the value of σ(30kN), the more preferred it is, but typically the upper limit is about 100mS / cm.
[0063] From the viewpoint of improving adhesion, the elastic modulus of the present solid electrolyte is preferably less than 50 GPa, more preferably less than 40 GPa, and more preferably less than 30 GPa. From the viewpoint of shape retention after molding, the elastic modulus is preferably more than 1 GPa, more preferably more than 2 GPa, and more preferably more than 5 GPa. The elastic modulus can be measured, for example, using a nanoindenter.
[0064] In the present solid electrolyte, from the viewpoint of achieving high lithium ion conductivity and more effectively obtaining the effect of the present invention, the proportion of the argyrodite-type crystal structure is preferably 50% by mass or more, more preferably 65% by mass or more, and further preferably 80% by mass or more. In addition, the upper limit is not particularly limited and may be 100% by mass, but is generally 99% by mass or less. The proportion of the argyrodite-type crystal structure can be calculated as follows: an internal standard substance is contained, and after measurement by XRD and neutron beam scattering, the peak intensity is compared with that of the internal standard substance.
[0065] As substances that can be contained in the present solid electrolyte other than argyrodite-type crystals, for example, Li3PS4, Li4P2S6, Li2S, LiHa (Ha is at least one halogen element selected from F, Cl, Br, and I), etc. can be cited. In addition, other lithium ion conductive solid electrolytes can also be included. As other lithium ion conductive solid electrolytes, for example, glass containing Li, P, and S, and crystallized glass can be cited.
[0066] Among them, in the case where the present solid electrolyte further contains a substance having a bonding peak of S8 in the Raman spectrum or an endothermic peak of sulfur in the DSC curve in addition to the argyrodite-type crystals containing S8 in the crystal structure, the present solid electrolyte needs to be determined after removing the substance. It should be noted that the above-mentioned situation refers to, for example, the case where the present solid electrolyte further contains elemental sulfur (S8) in addition to the argyrodite-type crystals. It should be noted that in the solid electrolyte where the argyrodite-type crystals and S8 exist separately, the elemental sulfur (S8) present can be removed by, for example, a method of heat treatment at 300°C for 1 hour.
[0067] <Method for producing sulfide-based solid electrolyte>
[0068] The method for producing the present solid electrolyte is not particularly limited as long as it is a method that can obtain a solid electrolyte having the above-mentioned characteristics. For example, there can be cited a method that includes a step of heating and melting raw materials containing Li, P, S and Ha (heating and melting step), and the heating and melting is carried out in a gas environment containing sulfur element.
[0069] In addition, the method for producing the solid electrolyte may further include other appropriate steps, such as a step of cooling the molten liquid obtained by heating and melting (cooling step), a step of reheating the solid obtained by the cooling step (reheating step), a pulverizing step, a drying step, etc. Each step is described below.
[0070] (raw materials)
[0071] The raw material containing Li, P, S, and Ha means that a conventionally known substance can be used as a material for obtaining an argyrodite-type crystal containing Li, P, S, and Ha.
[0072] For example, a mixture of a compound containing Li (lithium), a compound containing P (phosphorus), a compound containing S (sulfur), and a compound containing Ha (halogen) can be mentioned.
[0073] Examples of the compound containing Li include lithium compounds such as lithium sulfide (Li 2 S) and lithium oxide (Li 2 O), and lithium metal alone.
[0074] Examples of the compound containing P include phosphorus sulfides such as phosphorus trisulfide (P2S3) and phosphorus pentasulfide (P2S5), and simple phosphorus.
[0075] Examples of the compound containing S include the above-mentioned lithium sulfide (Li2S), the above-mentioned phosphorus sulfide (P2S3, P2S5), hydrogen sulfide (H2S), and the like. Elemental sulfur may also be used.
[0076] Among the compounds containing Ha, examples of compounds containing Cl (chlorine) include lithium chloride (LiCl) and the like.
[0077] Among the compounds containing Ha, examples of compounds containing Br (bromine) include lithium bromide (LiBr) and the like.
[0078] Among them, as the raw material, a combination including lithium sulfide, phosphorus sulfide, and at least one of lithium chloride and lithium bromide is preferred.
[0079] These raw materials are very unstable in the atmosphere and react with water to decompose, generating hydrogen sulfide gas and causing oxidation. Therefore, it is preferable to mix them in an inert environment.
[0080] The raw materials may contain other substances (compounds etc.) as additives etc. in addition to the substances mentioned above.
[0081] For example, from the viewpoint of improving the glass formation state of the obtained sulfide-based solid electrolyte, the raw material may include sulfides such as SiS2, B2S3, GeS2, Al2S3, Ga2S3, SnS2, SnS, and ZnS2. In addition, from the viewpoint of imparting moisture resistance, the raw material may include oxides such as SiO2, B2O3, GeO2, Al2O3, Ga2O3, SnO2, SnO, and ZnO. These compounds may be used alone or in combination of two or more.
[0082] The amount of these compounds added is preferably 0.1% by weight or more, more preferably 0.5% by weight or more, relative to the total amount of the raw materials, and preferably 50% by weight or less, more preferably 40% by weight or less.
[0083] The mixing of raw materials can be carried out, for example, by mixing in a mortar, mixing using a medium such as a planetary ball mill, a pin mill, a powder mixer, a medium-free mixing such as air flow mixing, etc. The raw materials can also be amorphized by mixing before heating. In addition, for the purpose of obtaining an intermediate, etc., the raw materials can also be heat-treated before heating and melting.
[0084] (Heating and melting process)
[0085] In the heating and melting step, the above-mentioned raw materials are heated and melted in a gas atmosphere containing sulfur element.
[0086] The heating and melting is performed in a gas environment containing sulfur. Examples of the gas containing sulfur include sulfur gas, hydrogen sulfide gas, carbon disulfide gas, etc. From the perspective of effectively introducing S8 into the crystal structure, it is preferred to contain sulfur gas.
[0087] The gas containing sulfur element may be composed only of a gas compound containing sulfur element such as sulfur gas, hydrogen sulfide gas, carbon disulfide gas, etc., and preferably contains an inert gas such as N2 gas, argon gas, helium gas, etc. from the viewpoint of cost reduction and the viewpoint of being used as a carrier gas for transporting sulfur components. In addition, the gas containing sulfur element may also contain impurities derived from a sulfur source, etc., as long as it is within the range in which the present solid electrolyte can be obtained.
[0088] From the viewpoint of making the sulfur element in a sufficient amount and of advancing the reaction of introducing sulfur, the sulfur gas (S x The content of sulfur gas (x=2 to 8) is preferably 0.01 vol% or more, more preferably 0.1 vol% or more, and further preferably 0.2 vol% or more. In addition, the content of sulfur gas is 100 vol% or less, and from the viewpoint of cost reduction and the viewpoint of using an inert gas as a carrier gas, it is preferably 99 vol% or less, and more preferably 98 vol% or less. Sulfur gas (S x The content of (x=2 to 8)) can be measured by mass spectrometry gas chromatography.
[0089] The gas containing elemental sulfur can be obtained by heating a sulfur source. Therefore, the sulfur source is not particularly limited as long as it is elemental sulfur or a sulfur compound that can obtain a gas containing elemental sulfur by heating. Examples thereof include elemental sulfur, hydrogen sulfide, organic sulfur compounds such as carbon disulfide, iron sulfide (FeS, Fe2S3, FeS2, Fe 1-xS, etc.), bismuth sulfide (Bi2S3), copper sulfide (CuS, Cu2S, Cu 1-x S, etc.), polysulfides such as lithium polysulfide and sodium polysulfide, polysulfide ether, rubber vulcanized with sulfur, etc.
[0090] These sulfur sources are heated by a separately provided sulfur source heating unit to generate a gas containing sulfur element, and an inert gas such as N2 gas, argon gas, helium gas, etc. is transported to the heating and melting furnace as a carrier gas to obtain a gas environment containing sulfur element. By separating the sulfur source heating unit from the portion where the heating and melting process is performed, even if oxygen and water are contained in the introduced gas, they can react with the sulfur gas and be removed, thereby obtaining a high-quality and high-purity sulfide-based solid electrolyte with few impurities.
[0091] The temperature for heating the sulfur source can be appropriately selected depending on the type of sulfur source used. For example, when elemental sulfur is used as the sulfur source, the temperature is preferably 250° C. or higher and preferably 750° C. or lower.
[0092] Alternatively, a gas environment containing sulfur element can be obtained by transporting solid sulfur sources such as elemental sulfur, H2S, Bi2S3, iron sulfide, copper sulfide, CS2, etc. in a fine state such as powder to a heating melting furnace using a carrier gas flow.
[0093] Alternatively, it is also preferable to adjust the mixing ratio of the above-mentioned compounds and simple substances so that sulfur is excessive in the raw material, and to evaporate part of the sulfur component in the raw material during heating and melting, thereby obtaining a gas atmosphere containing sulfur element.
[0094] For example, the heating and melting process can be performed as follows. In a structure in which a sulfur source heating section and a section for performing the heating and melting process are separated, the sulfur source is heated in the sulfur source heating section to generate a gas containing sulfur. An amount of the gas containing sulfur corresponding to the required sulfur partial pressure is fed into the section for performing the heating and melting process to obtain a gas environment containing sulfur. The above-mentioned raw materials are heated and melted in this environment. At this time, the sulfur partial pressure in the gas environment containing sulfur is preferably 10 -3 ~10 0 atm.
[0095] By heating and melting the raw material in a gas atmosphere containing elemental sulfur, sulfur is introduced into the molten raw material, thereby making up for the sulfur component that is easily volatilized from the raw material and introducing a sufficient amount of sulfur into the present solid electrolyte.
[0096] At this time, the viscosity of the molten liquid of the raw material decreases due to the fluidization of the solid, and it becomes a highly homogenized state. Therefore, in the molten liquid of the raw material, the gas containing sulfur element has great solubility and diffusivity. By introducing sulfur in such a liquid phase state, it is not only a simple supplement of the sulfur component constituting the crystal, but also further introducing S8 into the crystal structure, and it is believed that the present solid electrolyte can be obtained. In addition, by introducing sulfur in a liquid phase state, the homogeneity of the composition of the obtained solid electrolyte is easily improved, and S8 can be uniformly dispersed and contained in the crystal structure. It should be noted that containing S8 molecules in the crystal structure means that in addition to the situation where S8 molecules enter the interior of the crystal structure and are contained, it also includes the situation where S8 molecules exist outside the argyrodite-type crystal structure but are contained in a state uniformly dispersed in the grain boundaries of the crystals.
[0097] Furthermore, it is preferred to heat and melt the melt while stirring the molten metal or the gas containing sulfur element, because this makes it easier to obtain the effect of introducing sulfur and the effect of improving homogeneity.
[0098] In order to improve the fluidity of the melt and advance the reaction of introducing sulfur, the heating and melting temperature is preferably 600° C. or higher, more preferably 630° C. or higher, and further preferably 650° C. or higher. In addition, from the viewpoint of suppressing the degradation and decomposition of the components in the melt due to heating, the heating and melting temperature is preferably 900° C. or lower, more preferably 850° C. or lower, and further preferably 800° C. or lower.
[0099] In order to allow the reaction of introducing sulfur to proceed, the heating and melting time is preferably 0.1 hours or more, more preferably 0.5 hours or more, further preferably 0.7 hours or more, and further preferably 1 hour or more. In addition, from the viewpoint of suppressing the degradation and decomposition of the components in the melt due to heating, the heating and melting time is preferably 10 hours or less, more preferably 9.5 hours or less, and further preferably 9 hours or less.
[0100] The pressure during heating and melting is not particularly limited, but is preferably normal pressure to slightly increased pressure, and more preferably normal pressure. -3 ~10 0 By setting the sulfur partial pressure to such a level, the device does not become complicated, sulfur can be introduced efficiently at low cost, and the target sulfide-based solid electrolyte can be easily obtained.
[0101] From the viewpoint of preventing side reactions with water vapor, oxygen, etc. during heating and melting, the dew point is preferably -20°C or lower, and the lower limit is not particularly limited, but is generally about -80°C. In addition, the oxygen concentration is preferably 1000 ppm (volume basis) or lower.
[0102] The specific method during heating and melting is not particularly limited, and for example, a method of placing the raw material in a heat-resistant container and heating it in a heating furnace can be cited. As the heat-resistant container, there is no particular limitation, and heat-resistant containers made of carbon, quartz, quartz glass, borosilicate glass, aluminosilicate glass, heat-resistant containers containing oxides such as aluminum oxide, zirconium oxide, and mullite, heat-resistant containers containing nitrides such as silicon nitride and boron nitride, heat-resistant containers containing carbides such as silicon carbide, etc. can be cited. In addition, these heat-resistant containers can be formed into blocks by the above-mentioned materials, or can be containers formed with layers such as carbon, oxides, nitrides, and carbides. In addition, heating can also be performed in a vacuum-sealed state.
[0103] (Cooling process)
[0104] The method for producing the solid electrolyte preferably further comprises a step of cooling the melt obtained by heating and melting to obtain a solid. The cooling can be performed by a known method, and the method is not particularly limited.
[0105] From the viewpoint of maintaining the composition obtained by the heating and melting step, the cooling rate is preferably 0.01°C / sec or more, more preferably 0.05°C / sec or more, and further preferably 0.1°C / sec or more. In addition, the upper limit of the cooling rate is not particularly limited, and the cooling rate of the twin rolls, which is generally known as the fastest cooling rate, is 1,000,000°C / sec or less.
[0106] Here, when the obtained solid is intended to be an amorphous sulfide-based solid electrolyte, it is preferred to rapidly cool the melt obtained by heating and melting to obtain a solid. Specifically, the cooling rate in the case of rapid cooling is preferably 500°C / sec or more, more preferably 700°C / sec or more. In addition, the upper limit of the cooling rate is not particularly limited, and the cooling rate of the twin rolls, which is generally known as the fastest cooling rate, is 1,000,000°C / sec or less.
[0107] It should be noted that, by performing slow cooling during the cooling process to crystallize at least a portion of the solid, a sulfide-based solid electrolyte having a desired crystal structure or a sulfide-based solid electrolyte composed of a crystalline phase and an amorphous phase can also be obtained. The cooling rate in the case of slow cooling is preferably 0.01°C / sec or more, more preferably 0.05°C / sec or more. In addition, the cooling rate is preferably 500°C / sec or less, more preferably 450°C / sec or less. It should be noted that the cooling rate can be appropriately adjusted according to the conditions of crystallization.
[0108] (Reheating process)
[0109] An amorphous sulfide solid electrolyte or a sulfide solid electrolyte containing an amorphous phase can be subjected to a heat treatment (post-annealing) to promote high-temperature crystallization. In the method for manufacturing the solid electrolyte, when the solid obtained in the cooling step is an amorphous sulfide solid electrolyte, a sulfide solid electrolyte containing a crystalline phase can be obtained by reheating the solid. Alternatively, when the solid obtained in the cooling step is, for example, a sulfide solid electrolyte containing an amorphous phase and a crystalline phase, a step of reheating the solid may be further included as needed.
[0110] The method for producing the solid electrolyte may further include a step of pulverizing the sulfide-based solid electrolyte obtained in the above step, a step of drying the sulfide-based solid electrolyte, etc., depending on the application of the obtained sulfide-based solid electrolyte. These specific methods are not limited and can be carried out by known methods.
[0111] (Solid electrolyte layer, lithium ion secondary battery)
[0112] The present solid electrolyte has excellent adhesion when it is made into a powder compact from a powder state, and therefore, when it is processed into a powder compact in the form of granules, layers (sheets), or the like, good lithium ion conductivity can be obtained.
[0113] Therefore, the present solid electrolyte can be preferably used for a solid electrolyte layer used in a lithium ion secondary battery. The solid electrolyte layer may contain other components such as a binder as needed. The binder and other components may use conventionally known substances.
[0114] The content of the solid electrolyte relative to the entire solid electrolyte layer is preferably 80% by mass or more, more preferably 90% by mass or more. The solid electrolyte has excellent adhesion, so the content of components added to supplement the adhesion such as a binder can be reduced, making it easy to increase the lithium ion conductivity of the solid electrolyte layer.
[0115] The method for forming the solid electrolyte layer can use an existing known method. For example, a solid electrolyte powder can be dry-pressed on the surface of a positive electrode or a negative electrode to form a solid electrolyte layer. In addition, the components constituting the solid electrolyte layer can also be dispersed or dissolved in a solvent to form a slurry, applied in a layer (sheet), dried, and pressed arbitrarily. In addition, a solid electrolyte layer can also be formed on other substrates and transferred to the surface of a positive electrode or a negative electrode.
[0116] Regardless of which method is used to form the solid electrolyte layer, in the solid electrolyte layer using the present solid electrolyte, the adhesion between the particles of the solid electrolyte powder in the layer, or the adhesion between the particles of the solid electrolyte powder and other components is good, so it is easy to improve the lithium ion conductivity.
[0117] This solid electrolyte can be mixed with a positive electrode active material or a negative electrode active material and used as a positive electrode layer or a negative electrode layer. The positive electrode active material or the negative electrode active material, the current collector, the binder, the conductive aid, etc. used in the positive electrode layer or the negative electrode layer can use existing known substances. In the positive electrode layer and the negative electrode layer, by using this solid electrolyte, the adhesion between the particles of the solid electrolyte powder in the layer or the adhesion between the particles of the solid electrolyte powder and other components is good, and therefore, it is easy to improve lithium ion conductivity.
[0118] The structure of the lithium ion secondary battery containing the present solid electrolyte is not particularly limited, and for example, a fully solid lithium ion secondary battery containing a solid electrolyte layer, a positive electrode layer, and a negative electrode layer, and at least one of these layers contains the present solid electrolyte. According to the lithium ion secondary battery containing the present solid electrolyte, in the lithium ion secondary battery, the adhesion between the particles of the solid electrolyte powder or the adhesion between the particles of the solid electrolyte powder and other components is good, so it is easy to improve the lithium ion conductivity, and it can be expected that the battery characteristics will be improved.
[0119] The material of the outer package of the lithium ion secondary battery can also use existing known substances. The shape of the lithium ion secondary battery can also use existing known substances, for example, coin-shaped, sheet-shaped (membrane-shaped), folded, wound-type bottomed cylindrical, button-shaped, etc. can be appropriately selected according to the purpose, and can be appropriately selected according to the purpose.
[0120] Example
[0121] Hereinafter, the present invention will be specifically described with reference to Examples, but the present invention is not limited thereto. Examples 1 to 5 are Examples, and Examples 6 to 9 are Comparative Examples.
[0122] [evaluate]
[0123] (Powder X-ray Diffraction)
[0124] XRD measurement was performed under the following conditions to obtain an XRD pattern and analyze the crystal structure.
[0125] Device: Rigaku Corporation, SmartLab
[0126] Radiation source: CuKα radiation Scanning angle: 10-100°, scanning speed: 5° / min, number of steps: 0.01° / step.
[0127] Since the sulfide-based solid electrolyte as the measurement sample deteriorates when exposed to the atmosphere, the sample was prepared in an environment not exposed to the atmosphere and subjected to measurement.
[0128] Sample preparation: Sulfide-based solid electrolyte powder pulverized in a mortar was passed through a sieve with a mesh size of 100 μm to prepare a sulfide-based solid electrolyte powder having a particle size distribution with an average particle size of 5 to 10 μm. It should be noted that the particle size distribution was measured using a laser diffraction particle size distribution measuring device MT3300EXII manufactured by Microtrac, and the average particle size was measured from the obtained volume-based particle size distribution graph.
[0129] (Composition Analysis)
[0130] The solid electrolyte powder weighed in the glove box was dissolved in an alkaline aqueous solution, and the elements P and S were analyzed by ICP emission spectrometry, the element Li was analyzed by atomic absorption spectrometry, and the elements Cl and Br were analyzed by ion chromatography, thereby performing composition analysis.
[0131] (Raman spectroscopy)
[0132] Raman spectrometry was performed under the following conditions to obtain a Raman spectrum and confirm the presence or absence of an S8 bonding peak. The measurement was performed in an environment without exposure to the atmosphere.
[0133] In Table 1, at Raman shifts of 140 to 170 cm -1 、205~235cm -1 and 460~490cm -1 When at least one of the peaks is confirmed, the S8 bonding peak is "present". On the other hand, when these peaks are not confirmed, the S8 bonding peak is "absent". In addition, for the example where the S8 bonding peak is "present", the peaks at 420 to 440 cm are calculated based on the obtained Raman spectrum. -1 From PS4 3- The peak intensity (I A ) and 460~490cm -1 The peak intensity from S8 (I B ) B / I A .
[0134] Device name: Manufactured by Horiba Manufacturing Co., Ltd., LabRAM HR Evolution
[0135] Excitation light wavelength: 532nm, power during sample irradiation: 1-3mW, objective lens: ×10, confocal pinhole: 200μm, grating: 1200gr / mm, accumulation times: 2 seconds × 10 times, the measurement points are the average of 10 points.
[0136] (DSC measurement)
[0137] DSC measurement was performed using a differential scanning calorimeter under the following conditions to obtain a DSC curve, and the presence or absence of an endothermic peak of sulfur in the range of 70 to 160°C was confirmed.
[0138] In Table 1, when the endothermic peak of sulfur was confirmed, the value was “yes”, and when it was not confirmed, the value was “no”. The measurement was performed in an environment without exposure to the air.
[0139] Device name: DSC3300 manufactured by BRUKER AXS, sample amount: 20 mg, heating rate: 5°C / min, measurement temperature range: 25°C to 300°C.
[0140] (Lithium ion conductivity measurement)
[0141] Using 100 mg of the sulfide-based solid electrolyte powder, a powder compact (granule 1) with a diameter of 1 cm was prepared at a pressure of 10 kN. Similarly, a powder compact (granule 2) with a diameter of 1 cm was prepared at a pressure of 30 kN.
[0142] The lithium ion conductivity of each of these particles was measured by an alternating current impedance method (manufactured by Bio-Logic Sciences Instruments, potentiostat / galvanostat VSP, measuring frequency: 1 MHz to 100 Hz) at 25° C. The ratio of the lithium ion conductivity σ (30 kN) of particle 2 to the lithium ion conductivity σ (10 kN) of particle 1, σ (30 kN) / σ (10 kN), is shown in Table 1.
[0143] In addition, Table 1 shows σ(30 kN) as the lithium ion conductivity of each sulfide-based solid electrolyte.
[0144] [Example 1]
[0145] In order to obtain a sulfur-containing gas environment during heating and melting, Li6PS 5.3 Cl (sulfur excess) was used as the target composition. Lithium sulfide powder (manufactured by Sigma, purity 99.98%), phosphorus pentasulfide powder (manufactured by Sigma, purity 99%), sulfur (manufactured by Sigma, purity 99.99%) and lithium chloride powder (manufactured by Sigma, purity 99.99%) were weighed in a dry nitrogen environment and mixed at 400 rpm for 4 hours using a planetary ball mill in the same environment.
[0146] (Heating and melting process)
[0147] The obtained raw material mixture was placed in a heat-resistant container and heated and melted at 750° C. for 1 hour in an environment with a dew point of −60° C.
[0148] (Cooling process)
[0149] Thereafter, the solid is cooled at a cooling rate of 1 to 1000°C / sec to obtain a solid sulfide-based solid electrolyte containing an amorphous phase and an argyrodite-type crystal phase. 6.01 PS 5.25 Cl 0.99 The obtained powder had an average particle size of 5 μm.
[0150] [Example 2]
[0151] Taking Li6PS5Cl as the target composition, lithium sulfide powder (manufactured by Sigma, purity 99.98%), phosphorus pentasulfide powder (manufactured by Sigma, purity 99%) and lithium chloride powder (manufactured by Sigma, purity 99.99%) were weighed in a dry nitrogen environment and heated at 300°C for 1 hour in the same environment.
[0152] (Heating and melting process)
[0153] The obtained compound was placed in a heat-resistant container and heated and melted at 730°C for 30 minutes in an environment with a dew point of -60°C. At this time, elemental sulfur was heated at a temperature of 350°C, and the obtained sulfur gas was supplied together with N2 as a carrier gas at a partial pressure of 0.1 atm of sulfur gas to obtain a gas environment containing sulfur element, and the sulfur was heated and melted in this gas environment, thereby introducing sulfur into the melt. The content of sulfur gas in the gas environment containing sulfur element was 0.1 vol%.
[0154] (Cooling process)
[0155] Thereafter, the solid is cooled at a cooling rate of 1 to 1000°C / sec to obtain a solid sulfide-based solid electrolyte containing an amorphous phase and an argyrodite-type crystal phase. 6.05 PS 6.04 Cl 1.11 The sulfide-based solid electrolyte was crushed in an agate mortar to obtain a powder with an average particle size of 5 μm.
[0156] [Example 3]
[0157] The same procedure as in Example 1 was carried out except that the mixing ratio of the raw materials was changed to obtain a sulfide-based solid electrolyte Li 5.45 PS 4.72 Cl 1.70 In order to obtain a gas atmosphere containing sulfur during heating and melting, the raw materials were mixed in a ratio in which sulfur was excessive. After pulverization in the same manner as in Example 1, the average particle size of the obtained powder was 4 μm.
[0158] [Example 4]
[0159] The same procedure as in Example 2 was carried out except that the mixing ratio of the raw materials was changed to obtain a sulfide-based solid electrolyte Li 5.47 PS 4.79 Cl 1.72 After pulverization in the same manner as in Example 2, the average particle size of the obtained powder was 4 μm.
[0160] [Example 5]
[0161] The same procedure as in Example 2 was carried out except that the mixing ratio of the raw materials was changed to obtain a sulfide-based solid electrolyte Li 5.52 PS 4.89 Cl 1.01 Br 0.63 After pulverization in the same manner as in Example 2, the average particle size of the obtained powder was 5 μm.
[0162] [Example 6]
[0163] The raw materials were prepared in the same manner as in Example 1 except that the mixing ratio of the raw materials was changed. The raw materials were placed in a carbon container and further heated and calcined at 550° C. for 5 hours in a sealed state to perform a solid phase reaction. A sulfide solid electrolyte Li 5.94 PS 4.94 Cl 1.05 The heating and cooling rates were set to 5°C / min. The obtained sulfide-based solid electrolyte was pulverized using an agate mortar. The average particle size of the obtained powder was 6 μm.
[0164] [Example 7]
[0165] The same procedure as in Example 6 was carried out except that the mixing ratio of the raw materials was changed to obtain a sulfide-based solid electrolyte Li 5.40 PS 4.37 Cl 1.63 After pulverization in the same manner as in Example 6, the average particle size of the obtained powder was 6 μm.
[0166] [Example 8]
[0167] The sulfide-based solid electrolyte Li6PS5Cl+S was obtained by the same method as in Example 6 except that sulfur powder was added before heating and calcining. 0.5 .
[0168] After pulverization in the same manner as in Example 6, the average particle size of the obtained powder was 5 μm.
[0169] [Example 9]
[0170] The raw materials were prepared in the same manner as in Example 1. The raw materials were vacuum sealed in a quartz tube coated with carbon and heated at 550°C for 5 hours to perform a solid phase reaction. The raw materials were then taken out, pelletized, and vacuum sealed in a quartz tube coated with carbon again, and heat treated at 650°C for 30 minutes to obtain a sulfide-based solid electrolyte Li 6.11 PS 4.83 Cl 1.07 The obtained sulfide-based solid electrolyte was pulverized using an agate mortar. The average particle size of the obtained powder after pulverization was 5 μm.
[0171] The results of XRD measurement showed that the sulfide-based solid electrolytes obtained in Examples 1 to 9 all had an argyrodite-type crystal structure. The composition of the crystal structure of each example obtained by composition analysis is shown in Table 1. In addition, the results of Raman spectroscopy measurement, DSC measurement, and lithium ion conductivity measurement for the sulfide-based solid electrolyte of each example are shown in Table 1.
[0172]
Table 1
[0173]
[0174] The sulfide-based solid electrolytes of Examples 1 to 5 as embodiments have S8 bonding peaks confirmed in the Raman spectrum, but no endothermic peaks attributable to the phase change and melting of sulfur have been confirmed in the DSC curve. Therefore, it can be considered that the S8 molecules are uniformly dispersed in the argyrodite-type crystal structure. On the other hand, the sulfide-based solid electrolytes of Examples 6, 7, and 9 as comparative examples have no S8 bonding peaks confirmed in the Raman spectrum, and can be considered to contain sulfur in the S8 state. In addition, although the S8 bonding peak of the sulfide-based solid electrolyte of Example 8 has been confirmed in the Raman spectrum, the endothermic peak of sulfur has also been confirmed in the DSC curve. Therefore, although the sulfide-based solid electrolyte of Example 8 contains S8 molecules, the S8 molecules are not dispersed in the crystal structure, and it can be considered that they are separated from the crystal structure and exist in the form of a group of S8 molecules.
[0175] Compared with Examples 6 to 9 as comparative examples, Examples 1 to 5 as embodiments have a smaller σ(30 kN) / σ(10 kN), and the adhesion when the powder is made into a compressed powder body from a powder state is good. In addition, when comparing the embodiments and comparative examples with the same type (Cl) of Ha and a similar content ratio, that is, comparing Examples 1 and 2 with Examples 6, 8, and 9, or Examples 3 and 4 with Example 7, the lithium ion conductivity of the compressed powder body in the embodiments is more excellent. If such a solid electrolyte is processed into a granular, layered (sheet-like) or other compressed powder body and used in lithium ion secondary batteries, etc., it can be expected to improve the battery characteristics of lithium ion secondary batteries.
[0176] Although the present invention has been described with reference to details or specific embodiments, it is clear to those skilled in the art that various changes and modifications can be implemented without departing from the spirit and scope of the present invention. This application is based on Japanese patent application (Japanese Patent Application No. 2020-188040) filed on November 11, 2020, the contents of which are incorporated herein by reference.
Claims
1. A sulfide-based solid electrolyte, which is a sulfide-based solid electrolyte used in a lithium-ion secondary battery, Contains an Argentite-type crystal structure containing Li, P, S and Ha, The Ha is at least one selected from F, Cl, Br, and I, In the Raman spectrum obtained by Raman spectroscopy, the -1 、205~235cm -1 and 460~490cm -1 There is a peak at least at one of In the DSC curve obtained by differential scanning calorimetry (DSC), there is no endothermic peak in the range of 70 to 160°C. The sulfur S8 molecules are uniformly dispersed and present in at least one of the interior of the crystal structure and the grain boundaries between crystals.
2. The sulfide-based solid electrolyte according to claim 1, wherein The composition of the crystal structure is Li a PS b Ha c It means that 5≤a≤7, 4≤b≤6 and 0<c≤2.
3. The sulfide-based solid electrolyte according to claim 1 or 2, wherein In the Raman spectrum, 420-440cm -1 The peak intensity I A and 460~490cm -1 The peak intensity I B Ratio I B / I A It is 0.005 or more.
4. The sulfide-based solid electrolyte according to any one of claims 1 to 3, wherein When the powder is made into a powder with an average particle size of 2 to 10 μm, The ratio σ(30kN) / σ(10kN) of the lithium ion conductivity σ(30kN) at 25°C when the powder is pressed into a powder body at a pressure of 30kN to the lithium ion conductivity σ(10kN) at 25°C when the powder is pressed into a powder body at a pressure of 10kN is 1.34 or less.
5. The sulfide-based solid electrolyte according to any one of claims 1 to 4, wherein The elastic modulus is 5~40GPa. 6 . A solid electrolyte layer comprising the sulfide-based solid electrolyte according to claim 1 . 7 . A lithium ion secondary battery comprising the sulfide-based solid electrolyte according to claim 1 .
